Identifikasi Sebaran Rumah Gadang Pada Perkampungan Adat Sijunjung, Nagari Padang Ranah - Ariyati Ariyati; Nadya Bestnissa; Al Busyra Fuadi (Universitas Batanghari Jambi, 2026)
Vernacular architecture represents a form of design deeply rooted in the physical, material, and cultural context of its environment. This study explores the relationship between the architectural form of the Rumah Gadang and the geographical as well as cultural conditions of the Sijunjung Traditional Village, located in Nagari Padang Ranah. The main objective of this research is to identify the spatial distribution of Rumah Gadang, to analyze the correlation between tectonic aspects of the building and its site, and to uncover the underlying logic and abstract meaning behind the selection of materials, tools, and construction methods used by the local community. The research employs a qualitative approach through grounded theory, consisting of literature review, field observation, direct measurement, interviews with community leaders, and comparative architectural analysis. The findings reveal that there are 54 Rumah Gadang arranged linearly along the main circulation path rather than clustered by clan, deviating from the traditional spatial pattern of Minangkabau villages. This spatial arrangement indicates an adaptive response to the hilly topography and reflects a communal sense of togetherness among the residents. In conclusion, the architectural form of Rumah Gadang in Nagari Padang Ranah is not merely a cultural artifact but a manifestation of ecological awareness and social consciousness, representing the harmonious integration between people, place, and tradition within the framework of Minangkabau vernacular architecture.